Circulating MicroRNAs as biomarkers for disease staging in multiple sclerosis - Gandhi, Roopali; Healy, Brian; Gholipour, Taha; Egorova, Svetlana; Musallam, Alexander; Hussain, Mohammad Shuja; Nejad, Parham; Patel, Bonny; Hei, Hillary; Khoury, Samia; Quintana, Francisco; Kivisakk, Pia; et al. (Annals of neurology, 2013)
Objective MicroRNAs (miRNAs) are single‐stranded, small noncoding RNAs that regulate gene expression. Because they are stable in serum, they are being developed as biomarkers for cancer and other diseases. In multiple sclerosis (MS), miRNAs have been studied in cell populations but not in the circulation. In MS, a major challenge is to develop immune biomarkers to monitor disease. We asked whether circulating miRNAs could be identified in MS and whether they are linked to disease stage and/or disability. Methods A total of 368 miRNAs were measured in ethylenediaminetetraacetic acid plasma in 10 relapsing–remitting MS (RRMS) patients, 9 secondary progressive MS (SPMS) patients, and 9 healthy controls (HCs) using miRCURY LNA™ Universal RT microRNA polymerase chain reaction panels. Nineteen miRNAs from this discovery set were validated using qPCR on an independent set of 50 RRMS patients, 51 SPMS patients, and 32 HCs. Results We found that circulating miRNAs are differentially expressed in RRMS and SPMS versus HCs and in RRMS versus SPMS. We also found miRNAs to be linked to Expanded Disability Status Scale (EDSS). hsa‐miR‐92a‐1* was identified in the largest number of comparisons. It was different in RRMS versus SPMS, and RRMS versus HCs, and showed an association with EDSS and disease duration. miR‐92 has target genes involved in cell cycle regulation and cell signaling. The let‐7 family of miRNAs differentiated SPMS from HCs and RRMS from SPMS. let‐7 miRNAs regulate stem cell differentiation and T cell activation, activate Toll‐like receptor 7, and are linked to neurodegeneration. hsa‐miR‐454 differentiated RRMS from SPMS, and hsa‐miR‐145 differentiated RRMS from HCs and RRMS from SPMS. Interestingly, the same circulating miRNAs (let‐7 and miR‐92) that were differentially expressed in RRMS versus SPMS also differentiated amyotrophic lateral sclerosis (ALS) from RRMS subjects, but were not different between SPMS and ALS, suggesting that similar processes may occur in SPMS and ALS. Interpretation Our results establish circulating miRNAs as a readily accessible blood biomarker to monitor disease in MS. ANN NEUROL 2013;73:729–740